An evaluation of the timing of surgical complications following radical prostatectomy: Data from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP). Issue 3 (2nd July 2020) - Merhe, Ali; Abou Heidar, Nassib; Hout, Mohamad; Bustros, Gerges; Mailhac, Aurelie; Tamim, Hani; Wazzan, Wassim; Bulbul, Muhammad; Nasr, Rami
ABSTRACT: Objective: To perform a time-to-complication analysis for radical prostatectomy (RP) and computing risk factors for these complications, as RP is established as a first-line treatment for localised prostate cancer with excellent oncological outcomes but is not without its complications. Patients and methods: We used the National Surgical Quality Improvement Program (NSQIP) database to analyse data of patients who underwent RP, between 2008 and 2015, with the primary endpoint of time-to-complications. Categorical variables were analysed using descriptive statistics and continuous variables were recorded as medians and interquartile ranges (IQRs) such as timing of complications. Multivariable regression analyses were used to analyse time-to-complication and its effect on other outcomes. A P < 0.05 was defined as statistically significant. Results: The overall 30-day complication rate was 7.54% and was equally distributed before and after discharge. Bleeding/transfusion (3.37%), urinary tract infection (1.58%), deep venous thrombosis (DVT; 0.74%), and wound infection (1.08%) were the five most common complications after RP. The median (IQR) time-to-complication unique for each complication was: bleeding/transfusion occurred on the same operative day (1), renal complications occurred at 4 (2–6) days, sepsis at 12 (6.5–17.5) days, DVT at 11 (5.5–16.5) days, pneumonia at 4 (0.5–7.5) days, and cardiac arrest occurred at 5 (1.75–8.25) days. After discharge complications were associated with greater odds of re-admission (odds ratio [OR] 16.40, P < 0.001), but associated with a lesser length of stay (OR – 3.33, P < 0.001) when compared to pre-discharge complications. Conclusion: Several risk factors predict pre- and post-discharge complication rates. Knowledge regarding the timing of complications and their respective risk factors should improve patient–physician communication and prediction, and thus patient care. Abbreviations: ACS: American College of Surgeons; BMI: body mass index; DM: diabetes mellitus; DVT: deep venous thrombosis; Hct: haematocrit; IQR: interquartile range; LOS: length of stay; NSQIP: National Surgical Quality Improvement Program; OR: odds ratio; RP: radical prostatectomy